ARTIFICIAL INTELLIGENCE in LAW - GÖRENTAŞ, Muhammed Burak (SSD Journal, 2023)
Artificial intelligence is a field of computer science that involves creating and operating machines capable of intelligent behavior. Artificial intelligence is utilized in various fields such as medicine, finance, manufacturing, transportation, and entertainment. In the legal domain, artificial intelligence is now employed to analyze legal texts and decisions, determine legal trends, develop new legal concepts, conduct legal research, prepare legal documents, provide legal advice, process legal documents automatically, resolve legal disputes, manage legal cases, teach legal concepts to law students, analyze legal cases, and enhance legal skills. Additionally, artificial intelligence contributes to the development of applications that enable lawyers to be more efficient, effective, and successful. Artificial intelligence assists lawyers in conducting legal research, preparing legal documents, and offering legal advice. This enables lawyers to serve more clients and generate more revenue. While the use of artificial intelligence in the legal field is still in its infancy, its prevalence is expected to increase in the coming years, shaping the future of the legal system. However, it is crucial to consider the potential risks associated with the use of artificial intelligence. In particular, there are risks of reinforcing biases and potential misuse of artificial intelligence in violation of ethical principles within the legal system. The responsible development and use of artificial intelligence are essential. The use of artificial intelligence in the legal field should be approached with ethical considerations. The development and use of artificial intelligence systems should align with ethical principles. National and international organizations are working on defining ethical requirements for the use of artificial intelligence. In our country, legislative efforts for the use of artificial intelligence in all areas, especially in the legal field, should be undertaken as soon as possible.